Effect of applied potential on the microstructure, composition and corrosion resistance evolution of fluoride conversion film on AZ31 magnesium alloy. Issue 11 (November 2018) - Wu, Liping; Wang, Changgang; Pokharel, Durga Bhakta; Etim, Ini-Ibehe Nabuk; Zhao, Lin; Dong, Junhua; Ke, Wei; Chen, Nan
Abstract: AZ31 magnesium (Mg) alloy was potentiostatic polarized in 0.1 M deaerated KF solution with pH 7.5 from −0.4 V to −1.4 V with an interval of −0.2 V. The polarization process was described by the potentiostatic current decay. The resultant film was analyzed by scanning electron microscopy (SEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and electrochemical impedance spectroscopy (EIS). The results demonstrated that the deposited film included a Mg(OH)2 /MgF2 containing inner layer and a Mg(OH)2 /MgF2 /KMgF3 comprising outer layer. The high polarized potential produced high content of MgF2 but low content of KMgF3 and thin film. Conversely, the low polarized potential produced small content of MgF2 but high content of KMgF3 and thick film. The optimal corrosion resistance of the deposited film was obtained at −1.4 V, which was closely related with the content of MgF2 and KMgF3 and the film thickness.